Proximate Composition and Antioxidant Activity of Young Flattened Rice (Khao-Mao) - Preecharram, Sutthidech; Posoongnoen, Saijai; Thummawongsa, Theera; Sripakdee, Thitiya; Tawil, Sumana; Poomsuk, Nattawee; Jandaruang, Jinda (Trends in Sciences, 2023)
Khao-Mao producer group in Thailand’s Nakhon Phanom province’s Phon Sawan district, Na Hua Bo sub-district is a community that has produced Khao-Mao according to conventional wisdom, for a very long time. Khao-Mao has an emerald, green color, fragrant, delicate texture, and delicious taste, however the essential nutritional facts are not provided. Consequently, this study’s goal was to evaluate nutritional values by proximate analysis. All 6 types of young flattened rice-: Laos Wan, Kor Khor 6(RD6), Ai Lueng, San Pa Tong, Yee Pun, and Hom Nang Nuan have phenolic compounds by Folin-Ciocalteu method and antioxidant properties by 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. According to the findings, rice’s primary constituents are carbohydrates, which range from 69.76 to 73.07 %, protein, which ranges from 4.79 to 6.11 %, crude fat, which ranges from 1.68 to 2.22 %, fiber, which ranges from 0.00 to 0.03 % moisture, which ranges from 17.96 to 21.31 %, and ash, which ranges from 1.13 to 1.70 %. The San Pa Tong Khao-Mao has the highest 6.11% of protein content. Ai Lueng Khao-Mao has the greatest levels of total phenolic compounds, 0.79 mg/g dry weight. The DPPH radical scavenging assay test was used to measure the antioxidant activity. Their half-maximal inhibitory concentration (IC50) value falls between 1.18 and 2.00 mg/mL. The Hom Nang Nuan Khao-Mao has the lowest 1.18 mg/mL of IC50. According to the study’s findings, this community’s Khao-Mao has good nutritional and antioxidant properties. HIGHLIGHTS Khao-Mao has high proximate composition and high energy value Khao-Mao has relatively high quantities of protein and phenolic compounds Khao-Mao is a dish with a high-level antioxidant activity GRAPHICAL ABSTRACT